O mercado de trabalho nos arranjos produtivos brasileiros - Emiliano Felipe dos Santos Caruso (2007)
This study aims at analysing the job market of the brazilian APL's. It takes into consideration the socially deprived areas incorporating its unique social economic characteristics.Due to its complexity, we propose an exploratory analysis using the Grade of Membership method. This method classifies each individual person into an homogenic group. This, in turns, reduces the quantity to be analysed and allows better understanding of the unique characteristics of the data obtained by the Demographic Census and Municipal accounts, made available by IBGE and of the annual relation of social information offered by the Job and work Ministry and of the Atlas of human development in Brazil, published by the United Nations and the applied research institute and the foundation Joao Pinheiro using the year of 2000 data source. The results revealed that the deprived conditions of the location and the country do not allow that the externality be completely appropriated by firms or that its emergencies be compromised by local ambient fragilities, having significant impact in local business performance.